U-Pb SHRIMP zircon geochronology and T-t-d history of the Kampa Dome, southern Tibet - Quigley, M.; Liangjun, Y.; Gregory, Courtney; Corvino, A.; Sandiford, M.; Wilson, C.; Xiaohan, L. (Elsevier Science BV, 2008)
Structural, petrographic and geochronologic studies of the Kampa Dome provide insights into the tectonothermal evolution of orogenic crust exposed in the North Himalayan gneiss domes of southern Tibet. U–Pb ion microprobe dating of zircons from granite gneiss exposed at the deepest levels within the dome yields concordia 206Pb/238U age populations of 506 ± 3 Ma and 527 ± 6 Ma, with no evidence of new zircon growth during Himalayan orogenesis. However, the granite contains penetrative deformation fabrics that are also preserved in the overlying Paleozoic strata, implying that the Kampa granite is a Cambrian pluton that was strongly deformed and metamorphosed during Himalayan orogenesis. Zircons from deformed leucogranite sills that cross-cut Paleozoic metasedimentary rocks yield concordant Cambrian ages from oscillatory zoned cores and discordant ages ranging from ca. 491–32 Ma in metamict grains. Since these leucogranites clearly post-date the metasedimentary rocks they intrude, the zircons are interpreted as xenocrysts that are probably derived from the Kampa granite. The Kampa Dome formed via a series of progressive orogenic events including regional ~ N–S contraction and related crustal thickening (D1), predominately top-to-N ductile shearing and crustal extension (D2), top-to-N brittle–ductile faulting and related folding on the north limb of the dome, localized top-to-S faulting on the southern limb of the dome, and crustal doming (D3), and continued N–S contraction, E–W extension and doming (D4). Structural and geochronologic variability amongst adjacent North Himalayan gneiss domes may reflect changes in the magnitude of crustal exhumation along the North Himalayan antiform, possibly relating to differences in the mid-crustal geometry of the exhuming fault systems.